Personalized choice of vascular access for isolated hepatic perfusion: analysis of complication risk stratification programs - V. M. Unguryan; A. N. Kazantsev; A. V. Korotkikh; S. A. Ivanov; Yu. V. Belov; A. D. Kaprin (Российский кардиологический журнал)
The article presents three clinical reviews of isolated hepatic perfusion using a heart-lung machine. The probability of postoperative complications was retrospectively assessed using risk stratification programs for adverse outcomes. The conclusion is made about the effectiveness of the presented software.